Overexpression of MdATG8i improves water use efficiency in transgenic apple by modulating photosynthesis, osmotic balance, and autophagic activity under moderate water deficit. (1st April 2021) - Jia, Xin; Mao, Ke; Wang, Ping; Wang, Yu; Jia, Xumei; Huo, Liuqing; Sun, Xun; Che, Runmin; Gong, Xiaoqing; Ma, Fengwang
Abstract: Water deficit is one of the major limiting factors for apple ( Malus domestica ) production on the Loess Plateau, a major apple cultivation area in China. The identification of genes related to the regulation of water use efficiency (WUE) is a crucial aspect of crop breeding programs. As a conserved degradation and recycling mechanism in eukaryotes, autophagy has been reported to participate in various stress responses. However, the relationship between autophagy and WUE regulation has not been explored. We have shown that a crucial autophagy protein in apple, MdATG8i, plays a role in improving salt tolerance. Here, we explored its biological function in response to long-term moderate drought stress. The results showed that MdATG8i- overexpressing ( MdATG8i- OE) apple plants exhibited higher WUE than wild-type (WT) plants under long-term moderate drought conditions. Plant WUE can be increased by improving photosynthetic efficiency. Osmoregulation plays a critical role in plant stress resistance and adaptation. Under long-term drought conditions, the photosynthetic capacity and accumulation of sugar and amino acids were higher in MdATG8i- OE plants than in WT plants. The increased photosynthetic capacity in the OE plants could be attributed to their ability to maintain optimal stomatal aperture, organized chloroplasts, and strong antioxidant activity. MdATG8i overexpression also promoted autophagic activity, which was likely related to the changes described above. In summary, our results demonstrate that MdATG8i- OE apple lines exhibited higher WUE than WT under long-term moderate drought conditions because they maintained robust photosynthesis, effective osmotic adjustment processes, and strong autophagic activity.